PERBANDINGAN MORPHOMETRIK - MERISTIK JANTAN DAN BETINA IKAN KERLING (Tor tambroides) DARI DAS DI ACEH BARAT - Afrizal Hendri; Sri Wahyuni (Universitas Teuku Umar, 2016)
Kerling fish (Tor spp) is a species of freshwater fish, belonging to the family Cyprinidae. In Aceh Province there are three species of fish of very commercial i.e. Tor tambroides,Tor soro and Tor tambra. In this author's research focuses on Tor tambriodes. Survey results obtained by researchers in field description of the species is quite difficult to distinguish the character of males and females (unlike other Cyprinidae fish). Because that's what needs to be done comparative studies of characters within the same species morphometric and meristic approach. These are qualitative research (survey), is a method for the measurement of morphometric and character counting/meristic refers to the twinkle and Menezes (1974), and Jayaram (1981, 2002). The number of specimens to be analyzed i.e. 20 species (10 females: 10 males). The research results obtained that based on the characteristics of the morphometric there is no noticeable difference between females and males. However the qualitative character of morphometric visible presence of noticeable difference between females and males in character: body color, the profile of the muzzle, the thickness of the lips. While the study does not look meristic the existence of the real difference between females and males. Thus to view differences characterized the fish are females and the male Tor tambroides saw enough character body color (bright golden yellow: female, dark: male), the profile of the muzzle (convex: female, flat: male) and the profile lip up/down (thin, thick: females: males).